Intimate Partner Violence, prevalence and its consequences: a community-based study in Gambella, Ethiopia - Gedefa, Abdi Geda; Abdi, Tsegaye; Chilo, Desalegn; Debele, Gebiso Roba; Girma, Ayantu; Abdulahi, Misra (Frontiers in Public Health, 2024)
Intimate partner violence is defined as any behaviour by a current or past male intimate partner during marriage, cohabitation, or any other formal or informal union that causes physical, sexual, or psychological harm. Men are the most common perpetrators of this against women. It affects almost one-third of all women worldwide.Objective: This study aimed to assess the prevalence, consequences, and factors associated with intimate partner violence among partnered women in Gambella town.Methods: A community-based, cross-sectional study design was employed. A systematic random sampling technique was used to select the study participants. Data was collected using a pretested, structured questionnaire. The data were entered and analyzed using SPSS software version 25. The bivariate and multivariate logistic regression method was used to identify factors associated with intimate partner violence. Variables with a P-value <0.05 were considered significantly associated with the final model.The overall prevalence of intimate partner violence in the lifetime and the last 12 months was 58.8%, 95% CI (54.0, 63.6), and 51.8, 95% CI (46.7, 56.8), respectively. More than half (53.3%) of the violence resulted in physical injury, while 32.9% were separated from their partners whereas, mother's history of exposure to IPV [AOR: 1.